2012
DOI: 10.1111/dom.12032
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia risk with insulin degludec compared with insulin glargine in type 2 and type 1 diabetes: a pre‐planned meta‐analysis of phase 3 trials

Abstract: AimHypoglycaemia and the fear of hypoglycaemia are barriers to achieving normoglycaemia with insulin. Insulin degludec (IDeg) has an ultra-long and stable glucose-lowering effect, with low day-to-day variability. This pre-planned meta-analysis aimed to demonstrate the superiority of IDeg over insulin glargine (IGlar) in terms of fewer hypoglycaemic episodes at equivalent HbA1c in type 2 and type 1 diabetes mellitus (T2DM/T1DM).MethodsPooled patient-level data for self-reported hypoglycaemia from all seven (fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
313
2
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(357 citation statements)
references
References 27 publications
28
313
2
14
Order By: Relevance
“…The design of this post hoc analysis, including the segmentation of the overall trial period into titration (0-15 weeks) and maintenance (16-26 weeks) periods, matched that of an earlier preplanned meta-analysis of all IDeg phase 3a clinical trials (16).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of this post hoc analysis, including the segmentation of the overall trial period into titration (0-15 weeks) and maintenance (16-26 weeks) periods, matched that of an earlier preplanned meta-analysis of all IDeg phase 3a clinical trials (16).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The IDeg component in IDegAsp has been demonstrated to have a predictable glucose-lowering effect and up to four times lower day-to-day variability compared with insulin glargine at steadystate conditions (15). Clinical trials have demonstrated a lower risk of IDeg causing hypoglycemia compared with insulin glargine (16) and the possibility of flexibility in the timing of injections (17).…”
mentioning
confidence: 99%
“…In the population of subjects with T2DM, the rates of overall and nocturnal confirmed hypoglycemia were: 17% and 32% lower, respectively, across the entire treatment period; 25% and 38%, respectively, during the maintenance phase. 15 This pre-planned meta-analysis shows that similar improvements in HbA1c can be achieved with fewer hypoglycemic episodes, particularly nocturnal episodes, with IDeg than with IGlar across a broad spectrum of patients with diabetes (particularly T2DM patients), and insulin regimens. 15 Long-acting insulin analogues have been developed to cover the basal requirements of patients with diabetes but current treatment options generally require sometime-daily (or even twice-daily) administration to ensure optimal glycemic control.…”
Section: Efficacy and Safety Of Insulin Degludec In Subjects With Diamentioning
confidence: 83%
“…15 This pre-planned meta-analysis shows that similar improvements in HbA1c can be achieved with fewer hypoglycemic episodes, particularly nocturnal episodes, with IDeg than with IGlar across a broad spectrum of patients with diabetes (particularly T2DM patients), and insulin regimens. 15 Long-acting insulin analogues have been developed to cover the basal requirements of patients with diabetes but current treatment options generally require sometime-daily (or even twice-daily) administration to ensure optimal glycemic control. This schedule is often in conflict with everyday variations in patients' lives and can be challenging for patients.…”
Section: Efficacy and Safety Of Insulin Degludec In Subjects With Diamentioning
confidence: 83%
“…Insulin degludec has been clearly demonstrated to be equivalent to insulin glargine in lowering HbA 1c in key RCTs in both type 1 and type 2 diabetes (14,23,24). However, the risk of hypoglycemia, especially nocturnal hypoglycemia, was further reduced by ;25% during the maintenance period of the trials despite somewhat lower fasting plasma glucose concentrations (40). In addition, insulin degludec allows a more flexible approach to the timing of insulin administration to better accommodate the recipients' ever-changing daily life pattern (1,3,4,10,13,50,54).…”
Section: Arguments In Favor Of the New Insulinsmentioning
confidence: 99%